A refillable hyrdogel battery: Construction and characterization. (June 2019) - Jenson, Greg; Singh, Gurjap; Bhama, Jay K.; Ratner, Albert
Abstract: In this work, a hydrogel battery is designed, constructed, and tested. It is housed in a single glass container fitted with ports for filling, purging, and the electrical current collectors. The anode, cathode, and separator are all suspended in agar gel to maintain separation of the active components while allowing the exhausted battery chemicals to be removed with a syringe and new chemicals to be layered to restore potential. The active anode material consists of mMole quantities of hydrazine, while the active cathode material consists of mMole quantities of lithium perchlorate. The anode and cathode are suspended in an agar hydrogel with an acetylene black (AB) conductive additive separated by an NaCl (1.5 M) agar hydrogel. The battery was discharged across 10 MΩ resistors using current collectors of inconel wire or carbon rods, which yield comparable discharge curves. Peak closed circuit voltage (CCV), energy, and energy density from batteries constructed with 2, 4, 6, and 8 mMole anode and cathode maintain a positive trend.